If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + -1f = 2 Solving -16 + -1f = 2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -1f = 2 + 16 Combine like terms: -16 + 16 = 0 0 + -1f = 2 + 16 -1f = 2 + 16 Combine like terms: 2 + 16 = 18 -1f = 18 Divide each side by '-1'. f = -18 Simplifying f = -18
| 7(x+1)=2x+37 | | w-8+5=29 | | 5x+8-4x=1 | | x^2+-x-45=0 | | -8=3a-3 | | -14=2x+8 | | 0.3333333333333333b=4 | | 3+55x=33x+19 | | 5v+7(2.85)=28.70 | | 115=f+(f*.15) | | x^2+x-15=x-1 | | 29y-8b= | | 3x-3=7x-2x+1 | | 81=7x+2x | | 10+2(2a+1)=7a | | 9a+8= | | 4y+2y-30=18-2y | | (u-2)(u+4)=(u+6)(u-3) | | 5xy+3yx= | | 27b-9=45b+45 | | 3a^3=14a^2+24a | | -0.5x=26 | | s-15.50=47.50 | | u^2+2u-8=u^2+3u-18 | | 5x^2+x=11x | | -3t+5=2t+5 | | 4x+9+5x=12 | | 2(2x)-3.2x+2=0 | | -5[2k+5]=35 | | -37+5=2t+5 | | m(2m+9)=5 | | X+2.65=9.32 |